2018
DOI: 10.1504/ijleg.2018.090504
|View full text |Cite
|
Sign up to set email alerts
|

How logistics performance promote the international trade volume? A comparative analysis of developing and developed countries

Abstract: This paper analyses how logistics performance affects international trade volume and compares the different effects between developing and developed countries by employing a gravity model with panel data from 43 countries in 2010, 2012 and 2014. The findings show that an improvement of logistics performance index (LPI) has more impact on export volume than on import volume. And it has a more powerful influence on developed countries' trade volumes than on developing countries' trade volumes. To improve the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Martí, Puertas, and García (2014a) found that countries that improve their logistics performance also experienced increased trade. Wang and Choi (2018) confirmed that logistics performance benefits exports in developing economies, especially when improving customs clearance and infrastructure in these countries. Previously, Martí, Puertas, and García (2014b) evidenced the significance of logistics performance when dealing with complex goods.…”
Section: Logistics Performancementioning
confidence: 66%
“…Martí, Puertas, and García (2014a) found that countries that improve their logistics performance also experienced increased trade. Wang and Choi (2018) confirmed that logistics performance benefits exports in developing economies, especially when improving customs clearance and infrastructure in these countries. Previously, Martí, Puertas, and García (2014b) evidenced the significance of logistics performance when dealing with complex goods.…”
Section: Logistics Performancementioning
confidence: 66%
“…In the literature, there are studies dealing with the relationship between the logistics performance and trade (Martí et al, 2014a;Martí et al, 2014b;Puertas et al, 2014;Wang and Choi, 2018). These studies clearly show that logistics performance plays an important role in trade activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Martí et al (2014b) demonstrated the importance of logistics performance in facilitating trade. Wang and Choi (2018) determined that logistics performance is effective in increasing the volume of exports and imports with the panel data analysis method. Beysenbaev (2018) showed the logistics performances among the key factors that cause fluctuations in the trade volumes of the countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been determined that Japan, Germany, Togo, Benin, and the United States are the countries with the highest LCLP values. Wang and Choi (2018) examined the impact of the logistics performance of developed and developing countries on the export and import volumes of the countries. It has been understood that when the logistics performance improves, the countries are affected by the export volume more than the import volume.…”
Section: Logistics Performance Of the Nationsmentioning
confidence: 99%
“…These basic categories are "(i) customs, (ii) infrastructure, (iii) international shipment, (iv) logistics services, (v) track and trace, (vi) timeliness". It is known that academic studies benefit from logistics performance indicators published by LPI (Marti et al, 2014;Erkan, 2014;Ekici et al, 2016;Wang & Choi, 2018;Rashidi & Cullinane, 2019;Kabak et al, 2020). The frequent utilization of the LPI in the literature serves to legitimize its application as a performance indicator for countries' logistics performance.…”
Section: Introductionmentioning
confidence: 99%